2006
DOI: 10.1289/ehp.8035
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cadmium Levels in Pancreatic Cancer Patients from the East Nile Delta Region of Egypt

Abstract: The northeast Nile Delta region exhibits a high incidence of early-onset pancreatic cancer. It is well documented that this region has one of the highest levels of pollution in Egypt. Epidemiologic studies have suggested that cadmium, a prevalent pollutant in the northeast Nile Delta region, plays a role in the development of pancreatic cancer.Objective: We aimed to assess serum cadmium levels as markers of exposure in pancreatic cancer patients and noncancer comparison subjects from the same region in Egypt.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 58 publications
2
58
2
3
Order By: Relevance
“…An increase in urinary Cd by 1 lg/g creatinine was associated with a 35% increase in PSA levels, in subjects with a zinc intake below the median (12.7 mg/day). In a case-control study, pancreatic cancer was associated with serum Cd levels (Kriegel et al 2006). For each 1 lg Cd per l serum increase, the odds for pancreatic cancer increased with 12% (Table 3).…”
Section: Cancermentioning
confidence: 99%
“…An increase in urinary Cd by 1 lg/g creatinine was associated with a 35% increase in PSA levels, in subjects with a zinc intake below the median (12.7 mg/day). In a case-control study, pancreatic cancer was associated with serum Cd levels (Kriegel et al 2006). For each 1 lg Cd per l serum increase, the odds for pancreatic cancer increased with 12% (Table 3).…”
Section: Cancermentioning
confidence: 99%
“…Previous work in our laboratory has focused on the isolation/characterization of antibodies that bind to metal-chelate complexes and on the development of antibody-based assays useful for measuring a variety of heavy metals in a given sample (Khosraviani et al, 1998;Delehanty et al, 2003;Darwish and Blake, 2004;Kriegel et al, 2006;Zhu et al, 2007). The work described in this report represents some of the first experiments carried out by our laboratory in a field setting and demonstrates the portability, speed and overall utility of immunosensors for environmental analysis.…”
Section: Discussionmentioning
confidence: 91%
“…5 This finding was supported by a previous study by Kriegel et al, who found that East Nile Delta region in Egypt exhibited a high rate of young-onset pancreatic cancer (<65 years) which was associated with elevated serum cadmium and farming occupations. 6 They concluded that pancreatic cancer could occur at a younger age (<65 years) due to environmental exposure and also hereditary causes. 6 Regarding sex, the GLOBOCAN estimates for 2012 reported that the sex ratio of pancreatic cancer is close to one.…”
Section: Resultsmentioning
confidence: 99%
“…6 They concluded that pancreatic cancer could occur at a younger age (<65 years) due to environmental exposure and also hereditary causes. 6 Regarding sex, the GLOBOCAN estimates for 2012 reported that the sex ratio of pancreatic cancer is close to one. 1 So, it seems that the gap between age groups and sexes can be explained by differences in exposures such as smoking, hereditary causes and sex-specific risk factors that could be important in pancreatic carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%